Effectiveness of emotional self- regulation on marital self- regulation of the newly married couples - Ghezelseflo, Mehdi; Rostami, Mehdi; Saadati, Nadereh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to identify the effectiveness of emotional self- regulation on marital self- regulation of the newly married couples. Method: it was a quasi- experimental one with control, experimental group and pretest, posttest with a 3- month follow-up. The statistical population of this study was the newly married couples of Tehran, Al-Zahra and Shahid Beheshti University who were invited to cooperate in a public call to all students who had been married for less than 3 years thirty of them were being selected and randomly assigned to experimental (15 couples) and control (15 couples) groups. The experimental group received weekly intervention in 8 sessions of 90 minutes. Both groups were evaluated in three stage of pre-test, post-test and 3 month follow- up. Data were analyzed using mixed variance repeated measures. Results: The results showed a significant difference between the performance of two experimental and control groups in the relational self-regulation score (F= 27.54, P=0.001) and relational activity (F= 20.91, P= 0.001) Post- test and follow- up indicated. Conclusion: Since emotional self- regulation training enhances self- regulation of newly married couples, psychologists and counselors can benefit this method to assist the newly married couples.